THE EFFECT OF INDIVIDUAL COUNSELLING ON REDUCING STRESS LEVELS AMONG MOTHER WHO TAKES CARE CHILDREN WITH CEREBRAL PALSY - Arif Rohman Mansur (International Journal of Nursing and Health Services (IJNHS), 2019)
Physical limitations and problems related to child development Cerebral Palsy be a stressor for mothers to in everyday life, the conditions trigger high levels of stress in childcare. The study aimed to examine the effect of individual counseling on reducing the stress level among mothers who take care of children with cerebral palsy. Location of research in the State Special School (SLB). N 1 Bantul Regency. Fifteen mothers who have children with cerebral palsy were selected by purposive sampling. The results showed that there was a significant difference between before and receiving counseling program (p=0.804, t =0.253). In conclusion showed that there is no positive effect of counseling on reducing the stress level of mothers who take care of children with cerebral palsy. Children who have undergone the routine clinical assessment can increase the positive perception of parent or mother. Researchers recommend interventions provided with/for the subject of the research should emphasize the technical and cognitive aspects in caring for and educating children Cerebral Palsy